The ENOVAT survey on current methodologies used for bacterial identification and antimicrobial susceptibility testing in European veterinary diagnostic laboratories. - Timofte Dorina; Cvetkovikj, Iskra; Zendr Flavia; Blum Schlomo; Chaintoutis Serafeim; Koop Peter; Stritov Zrinka; Kittl Sonja; Zdovc Irena; Paulshus Erik; Koritnik Tom; Laconi Andrea; et al. (European Society of Veterinary Microbiology, 2022)
Background: Veterinary diagnostic laboratories (VDLs) play a key role in determining the aetiology of infectious diseases and antimicrobial stewardship. However, there is still a lack of harmonisation of methodologies and procedures used in European VDLs (1,2). Methods: The European Network for Optimization of Veterinary Antimicrobial Treatment (ENOVAT) designed a survey, which was distributed via a public online platform to VDLs in 34 European countries. The survey focused on practices and interpretive criteria used for culture and identification (C&ID), and antimicrobial susceptibility testing (AST) of veterinary bacterial pathogens. Results: Two hundred and ninety laboratories responded, representing a mixture of academic (39%), government (33%), and private (28%) laboratories. Average C&ID turnaround varied from 1-2 days (78%) to 3-5 days (20%), and 6-8 days (0.5%). For AST, similar time frames were achieved by 63%, 60%, and 0.5% of VDLs, respectively. Only 57% of laboratories attempted bacterial ID to species level. Biochemical ID systems (e.g., API kits) were the most used (56%) followed by MALDI-TOF MS (46%). For AST, Kirby-Bauer disc-diffusion (DD) and MIC determination were conducted by 44% and 33% of laboratories, respectively. A combination of EUCAST and CLSI clinical breakpoints was most commonly used for interpretation of both DD (41%) and MIC (47%). Only 48% and 46% of VDLs routinely screened isolates for methicillin resistance and ESBL production, respectively. Conclusion: A variety of methodologies were identified for C&ID and AST in European VDLs. Our results emphasize the need to harmonise methodologies and provide better guidelines, to ultimately improve animal and public health.
Keywords: ENOVAT, AST, antimicrobial stewardship